Ushering in participatory democracy on cyber waves of change? The possibilities of an interactive White House - Purnell, Amanda Lynn, author; Griffin, Cindy, advisor; Daum, Courtenay, committee member; Sprain, Leah, committee member (Colorado State University. Libraries, 2010)
This thesis seeks to understand in what ways the Obama administration uses web-based technologies to fulfill key campaign promises for transparency and participation, as well as how those strategies may foster participatory democracy. To answer these questions, the thesis engages conversations of interactivity, interpellation, participatory democracy and the role the net generation plays in the future of participatory democracy in the United States. The project considers two key features of WhiteHouse.gov—the Briefing Room and the Blog—as well as the administration's online presence on Facebook through their White House Live feature. It concludes that the administration is fulfilling most of their campaign promises, but not all of those promises have the capacity to promote participatory democracy. The American public has more access to their government, and to information, but has little actual influence in everyday governing. This thesis also suggests that the Obama administration is putting forth a new understanding of American citizenship that interpellates an active citizen. The characteristics the administration attributes to this active citizen align with the characteristics attributed to members of the net generation. The implications of these findings and the barriers to participatory democracy are discussed as the project concludes by considering the future of politics in the United States.
Keywords: communication systems; communication in politics; United States; direct democracy; government web sites; White House (Washington, D.C.); Internet in public administration; Internet